Comparison of Partial and Radical Laparascopic Nephrectomy: Long-Term Outcomes for Clinical T1b Renal Cell Carcinoma - Cai, Yi; Li, Han-Zhong; Zhang, Yu-Shi (Urology Journal, 2018)
Purpose: To compare the long-term clinical and oncologic outcomes in patients treated with laparoscopic partial nephrectomy (LPN) and laparoscopic radial nephrectomy (LRN) for clinical T1b renal cell carcinoma. Materials and Methods: We retrospectively reviewed the records of all patients who underwent LPN or LRN for a single clinical T1b tumor between January 2005 and January 2012, an actual follow-up of 2-year or greater was available in 39 and 160 after LPN and LRN, respectively. Survival was calculated using the Kaplan-Meier method. Multivariable Cox regression analysis was done to assess predictors of survival. Results: The two cohorts of patients were similar in age, sex, body-mass index and preoperative eGFR. There were no differences in tumors size (4.97 vs 5.29cm, P = .08), and pathological stage distribution between the two cohorts. The median follow-up after LPN and LRN were 67 (range: 18-118) and 70 (19-120) months, respectively. For LPN versus LRN, 5-years overall and cancer specific survival rates were 93.33% vs 85.69% and 96.00% vs 91.35%, respectively. For LPN versus LRN, 10-years overall and cancer specific survival rates were 85.56% vs 73.41% and 88.00% vs 82.85%, respectively. On multivariate analysis, patients’ age, ASA score and pathological stage were the major factors affecting overall survival, and patients’ age and pathological stage were associated with cancer specific survival. The percent decrease in glomerular filtration rate was significantly lower in the LRN group at early and last followup. Conclusion: LPN is an effective treatment option in appropriately selected patients with cT1b RCC. It provides 5-year, 10-year overall survival and cancer specific survival comparable to those of LRN as well as better preservation of renal function than LRN. Overall survival and cancer specific survival are associated with nonmodifiable factors but not by the choice of operative technique.